IL-1 family members in health and disease - Doyle, Sarah L.; Brint, Elizabeth; Kamradt, Thomas (My University, 2019)
In 1985, two distinct cDNAs encoding proteins sharing human Interleukin-1 (IL-1) activity were described, thus defining the first two members of the IL-1 family – IL-1α and IL-1β. These potent pro-inflammatory cytokines have been the subject of much research in the areas of fever, inflammation as well as their role in a myriad of inflammatory-associated diseases. Many related cytokines, with both pro- and anti-inflammatory properties, including IL-18, IL-33, IL-36, IL-37, IL-38, IL-1 receptor antagonist (IL-1Ra), and IL-36Ra, have since been identified. In addition to the 11 identified cytokine members of this family, there are now multiple discrete receptor family members, comprising functional receptors that are able to activate downstream signalling cascades, as well as several decoy and inhibitory receptors. Whilst IL-1 has been identified for several decades, new information concerning its role in disease is constantly emerging. In addition, many members of this family have now been identified as being critical for the development of diverse inflammatory and allergic diseases. In this Research Topic, we aim to gather a series of articles that discuss IL-1 biology; the signaling pathways activated by IL-1 family members and negative regulation of these pathways. Given the recent explosion of this field in terms of the more novel members of this family e.g. IL-33 and IL-37, we also aim to cover studies that discuss newer family members and their role in specific diseases.
PUBLISHED
Keywords: IL-1; Cytokines; IL-1β; IL-1α; Inflammation; Immunology, Inflammation & Infection; CYTOKINE; CYTOKINE INTERLEUKIN-1-BETA; CYTOKINE RESPONSES; Health